Critical Review on Interrelationship of Electro-Devices in PV Solar Systems with Their Evolution and Future Prospects for MPPT Applications - Weng-Hooi Tan; Junita Mohamad-Saleh (Energies, 2023)
A photovoltaic (PV) system is composed of a PV panel, controller and boost converter. This review article presents a critical review, contributing to a better understanding of the interrelationship of all these internal devices in the PV system, their respective layouts, fundamental working principles, and architectural effects. The PV panel is a power-generating device. A controller is an electronic device that controls the circulating circuits in a PV system to collect as much PV output as possible from the solar panel. The boost converter is an intermediate device that regulates the PV output based on the duty cycle provided by the controller. This review article also updates readers on the latest information regarding the technological evolution of these interconnected devices, along with their predicted future scope and challenges. Regarding the research on PV panels, this paper explains in depth the mathematical modeling of PV cells, the evolution of solar cell technology over generations, and their future prospects predicted based on the collected evidence. Then, connection patterns of PV modules are studied to better understand the effect of PV array configuration on photovoltaic performance. For the controller, state-of-the-art maximum power point tracking (MPPT) techniques are reviewed under the classification to reveal near-term trends in MPPT applications. On the other hand, various converter topologies proposed from 2020 to 2022 are reviewed in terms of tested frequency, voltage gain, and peak efficiency to comprehend recent evolution trends and future challenges. All presented information is intended to facilitate and motivate researchers to deepen relevant applications in the future.